Answer:
y = - 8
Explanation:
Using the rule of exponents
=
![a^(mn)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y1umqrf7s4do08xjl3a1y1e5wom5ygzas5.png)
Note that 8 = 2³ and 16 =
![2^(4)](https://img.qammunity.org/2021/formulas/computers-and-technology/college/pks9n99pre6ht3o1j7gou1ijfuyfsgigpu.png)
Given
=
, then
=
![(2^4)^(y+2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9pqhl9g5qr12tp3igb2w6g5n65zf3w9f5f.png)
=
![2^(4(y+2))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9nca6nby3jjlvamosfi1wkqehwb7h99t17.png)
Since the bases on both sides are equal, both 2 then equate the exponents
4(y + 2) = 3y
4y + 8 = 3y ( subtract 3y from both sides )
y + 8 = 0 ( subtract 8 from both sides )
y = - 8